Descriptive Analysis of Brand Loyalty, Reputation, and Equity at Lantikya Store - Heni Nurlia Fatmawati; Wisnu Mahendri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to quantitatively describe the profile of customer loyalty, brand reputation, and brand equity at Lantikya Store Jombang. Amidst fierce competition in the retail business, a deep understanding of the actual condition of these key marketing variables is essential for formulating effective strategies. Using a descriptive research design with a quantitative approach, data was collected through questionnaires from 110 Lantikya Store customers selected using a probability sampling technique. Data analysis focused on descriptive statistics, including frequency, percentage, and mean values for each variable and its indicators. The results show that customer loyalty at Lantikya Store indicates a high level of agreement from respondents. Brand reputation is also strongly agreed upon by customers. Similarly, overall brand equity shows a high level of agreement. The demographic profile of respondents is dominated by female customers in the student age range. This research produces a detailed empirical portrait of Lantikya Store's customers, providing a data-driven basis for management to strengthen marketing strategies and maintain customer loyalty.